Parmenides and presocratic philosophy - Palmer, John Anderson, 1965- (Oxford : Oxford University Press, 2009)
Parmenides of Elea is generally considered the most profound & challenging of the pre-Socratic philosophers. John Palmer develops & defends a fundamentally original interpretation of Parmenides & his place in early Greek thought. An appendix presents a Greek text of the fragments of Parmenides' poem with English translation & notes.
Poem in Ancient Greek with English translation and notes.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Parmenides; Eleatics; Pre-Socratic philosophers